(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Hydropower potential studies usually include estimation of hydropower resources and creating propositions for hydropower development on study area. The current paper describes authors’ study, dedicated to development of methodological approaches and software designed for solving problems stated above. Process automation is achieved by using geographic information systems (GIS) and additional programs (Python language was used).Hydropower potential estimation is the key element for understanding future prospects of hydropower development within the study area. The latest large-scale hydropower potential studies of Russian territories were held in 1940-1980. In those times, such researches were carried out almost without any automation, so calculation process was time-consuming. As a result, only hydropower potential of large and several medium-sized rivers was estimated; hydropower potential assessments of small rivers were conducted only using approximate approach.Nowadays, implementation of technologies and software products, such as geographic information systems, contributes to development of methodologies, which can be used to automate business-processes in different scientific disciplines, including processes of hydropower potential estimation and prospective hydropower plants siting. In comparison with former studies, GIS allow to reduce labor work significantly and to perform analysis of large study areas and large number of streams (including small rivers) in relatively short time using up-to-date topographical, hydrological and hydrographical information.Authors have developed and tested methodological approach and GIS-tools for automated hydropower potential estimation. Re-estimation of hydropower potential was fulfilled by the authors for the most part of Russia. The data for more than 10 000 river’s was compared to the results of prior studies (data, such as river basin area, annual river flow, hydropower potential). The gross hydropower capacity of rivers and gross hydropower potential were estimated as 350 GW and 3,07*103 TWh respectively.The next step in hydropower potential studies is prospective hydropower plants siting. Authors developed methodological approach and GIS-tools to automate this process. The GIS-tools provide comparison of site alternatives based on their hydropower parameters; transport, infrastructure, electricity network proximity; topographic situation and other factors affecting site suitability. Algorithm of automation and results of the search siting are presented.